Depression and anxiety among Macau residents during the COVID-19 outbreak: A network analysis perspective - Sun, He-Li; Chen, Pen; Feng, Yuan; Si, Tong Leong; Lam, Mei Ieng; Lok, Ka-In; Chow, Ines Hang Iao; Su, Zhaohui; Cheung, Teris; Tang, Yi-Lang; Jackson, Todd; Sha, Sha; et al. (Frontiers in Psychiatry, 2023)
Background: The 2019 novel coronavirus disease (COVID-19) outbreak affected people’s lifestyles and increased their risk for depressive and anxiety symptoms (depression and anxiety, respectively hereafter). We assessed depression and anxiety in residents of Macau during “the 6.18 COVID-19 outbreak” period and explored inter-connections of different symptoms from the perspective of network analysis. Methods: In this cross-sectional study, 1,008 Macau residents completed an online survey comprising the nine-item Patient Health Questionnaire (PHQ-9) and seven-item Generalized Anxiety Disorder Scale (GAD-7) to measure depression and anxiety, respectively. Central and bridge symptoms of the depression-anxiety network model were evaluated based on Expected Influence (EI) statistics, while a bootstrap procedure was used to test the stability and accuracy of the network model. Results: Descriptive analyses indicated the prevalence of depression was 62.5% [95% confidence interval (CI)=59.47-65.44%)], the prevalence of anxiety was 50.2% [95%CI=47.12-53.28%)] and 45.1% [95%CI=42.09- 48.22%) of participants experienced comorbid depression and anxiety. “Nervousness-Uncontrollable worry” (GADC), “Irritability” (GAD6) and “Excessive worry” (GAD3) were the most central symptoms and “Irritability” (GAD6), “restlessness” (GAD5) and “Sad Mood” (PHQ2) were the key bridge symptoms that emerged in the network model. Conclusions: Nearly half of residents in Macau experienced comorbid depression and anxiety during the 6.18 COVID-19 outbreak. Central and bridge symptoms identified in this network analysis are specific targets for treatment and prevention of comorbid depression and anxiety related to this outbreak.